The keeper of lost things [large type] : a novel - Hogan, Ruth, 1961- (Thorndike Press, 2017)
Andrew Peardew collects things dropped or left behind by others and writing stories about them. He does this as a tribute to the fiancée who died the day he lost one of her keepsakes. When a dying Andrew bequeaths his estate to his assistant, Laura, she begins to bond with new neighbors while attempting to reunite the objects with their owners.